PASAR DAN HARGA DALAM EKONOMI ISLAM - Virgiawan, A. m. luthfi; Lutfi, Mukhtar; Wahab, Abdul; virgiawan, luthfi (LPPM STAI Muhammadiyah Probolinggo, 2026)
Market and price are essential components in the Islamic economic system, as they play a vital role in the distribution and exchange of goods and services. This study aims to analyze the concept of market and price determination mechanisms from the perspective of Islamic economics. The research employs a library research method by reviewing classical and contemporary Islamic economic literature. The findings indicate that Islam allows market mechanisms to operate naturally based on supply and demand, provided they adhere to principles of justice, honesty, and transparency. Practices that distort the market, such as usury, hoarding (ihtikar), and monopoly, are strictly prohibited. Government intervention is permissible when market distortions cause harm to the public. Therefore, market and price in Islamic economics are not solely profit-oriented but also emphasize social welfare and public benefit.